Cell division of Giardia intestinalis: flagellar developmental cycle involves transformation and exchange of flagella between mastigonts of a diplomonad cell - Nohynková, Eva; Tumová, Pavla; Kulda, Jaroslav (Eukaryotic cell, 2006)
Giardia intestinalis is a binucleated diplomonad possessing four pairs of flagella of distinct location and function. Its pathogenic potential depends on the integrity of a complex microtubular cytoskeleton that undergoes a profound but poorly understood reorganization during cell division. We examined the cell division of G. intestinalis with the aid of light and electron microscopy and immunofluorescence methods and present here new observations on the reorganization of the flagellar apparatus in the dividing Giardia. Our results demonstrated the presence of a flagellar maturation process during which the flagella migrate, assume different position, and transform to different flagellar types in progeny until their maturation is completed. For each newly assembled flagellum it takes three cell cycles to become mature. The mature flagellum of Giardia is the caudal one that possesses a privileged basal body at which the microtubules of the adhesive disk nucleate. In contrast to generally accepted assumption that each of the two diplomonad mastigonts develops separately, we found that they are developmentally linked, exchanging their cytoskeletal components at the early phase of mitosis. The presence of the flagellar maturation process in a metamonad protist Giardia suggests that the basal body or centriole maturation is a universal phenomenon that may represent one of the core processes in a eukaryotic cell.
Keywords: Fluorescent Antibody Technique; transmisní elektronová mikroskopie; Flagella; Microscopy, Confocal; flagella; Animals; Cell Division; Microscopy, Electron, Transmission; buněčné dělení; konfokální mikroskopie; zvířata; fluorescenční protilátková technika; Giardia lamblia